Identification of Saprophytic Mold Isolated from Mangrove Soil: A Review - Rahmawati, Hanif Nur; salsabila, Syarifah salsabila; Rahayuningtras, Nazil Dwi; Nurhariyati, Tri; Fatimah (Universitas Airlangga, 2023)
Saprophytic mold is one type of mold that has the ability to survive in extreme conditions, such as in mangrove soil. Saprophytic fungi act as the main organism in the process of decomposition of organic matter and energy flow in the mangrove area. Several researchers successfully identified 102 species and 33 genera of saprophytic fungi. Aspergillus is known to be the dominant mold on mangrove soils because of its characteristics, such as high sporulation and spore spread and its ability to withstand extreme environmental conditions. The use of saprophytic molds in biofertilizer manufacturing due to saprophytic molds can produce cellulase, xylinase, and ligninase enzymes to decompose organic matter and produce toxin compounds for pathogens in plants. The presence of mold species in mangrove soil is influenced by several factors, including the temperature level, season, the salinity of mangrove waters, soil pH, and oxygen.